SHEIKH IBRAHIM MUSA PARABEK’S THOUGHTS ON TASHYID AND TAWASSUL IN HIDĀYAH AL-ṢIBYĀN - Azhari, Nadyya Rahma (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2023)
The global reform of Islamic thought had impact of dividing the Minangkabau ulamas (Muslim scholars) into both “kaum tuo” as a traditionalist and “kaum mudo” as a modernist. Even today, the history of Minangkabau ulamas cannot be separated from this category. Ibrahim Musa is one of the ulamas who had unique position because of his affiliation to some groups. He also was recognized as “kaum mudo” due to his involvement in their movement. At the same time, other historical records showed his engagement with “kaum tuo.” His ambiguities in siding among Minangkabau ulamas are worth-investigating. This article seeks to analyze Ibrahim Musa’s thoughts based on his kitab, Hidāyah al-Ṣibyān. It argues that Ibrahim Musa did not clearly state his stance, except providing two views. Further, he was trying to explain their interpretations which proved that in the history of Islam in Minangkabau there are ulamas who cannot simply categorized as traditionalist or modernist due to the complexity of their thoughts of Islam. In this respect, the study of non-mainstream ulama figures like Ibrahim Musa is scholarly pivotal to construct the historiography of Minangkabau ulama as a whole.